Symptoms of generalized anxiety disorder and migraine in medical students from a private university in Metropolitan Lima - Loconi-Medina, Winnie (2025)
Objective: To determine the relationship between symptoms of generalized anxiety disorder (GAD) and migraine in medical students. Materials and methods: This is an analytical cross-sectional study. Sixth- and seventh-year medical students were invited to participate in the survey. Data collections were conducted through Google Forms. The questionnaire included sociodemographic factors, family history, the ALCOI-95 questionnaire, and the GAD-7 questionnaire. The ALCOI-95 questionnaire classified students into “non-migraine,” “migraine without aura,” or “migraine with aura”. The GAD-7 questionnaire classified students based on the severity of symptoms of GAD. Results: A response rate of 52 % was achieved. Forty-seven students (27.81 %) had migraine, of which 22 (13.02 %) had migraine without aura, and 25 (14.79 %) had migraine with aura. Sixty-one students (36.09 %) had minimal symptoms of GAD, 70 (41.42 %) had mild symptoms, 27 (15.98 %) had moderate symptoms, and 11 (6.51 %) had severe symptoms. A statistically significant relationship was found between migraine and GAD symptoms (p = 0.0001). Conclusion: The study found a statistically significant relationship between migraine and symptoms of GAD in medical students.